A narrative review on problems in product quality, regulatory system constraints, and the concept of quality by design as a solution for quality assurance of African medicines - Hassen, Hassen Kebede; Mekasha, Yesuneh Tefera; Tegegne, Addisu Afrassa; Ozalp, Yildiz (Frontiers in Medicine, 2024)
The provision of medicines with confirmed quality and efficacy is critical for maintaining the public health and building confidence in the healthcare systems.However, the presence of poor-qualtiymedicines still presents a significant challenge in the pharmaceutical landscape acroos the African regions. This is further exacerbated by the lack of consistency or discrepancy in the current regulatory framework. As a consequence, given the current constraints, a robust regulatory structure that can guarantee the supply chains attainment of the intended medicinal product requirements are required. The review portrays the prevalence of poor-quality medicinal products in various regions of Africa. Among various categories of findings, 42% of the reports on poor-quality medicinal products come from the African region, as per the WHO report. Furthermore, separate findings on substandard medicinal products from many African countries were encountered. The presence of problems in the regulatory system, such as the absence of any pharmacopeia belonging to any African country and variation/inconsistency in each country's regulatory set-up, was indicated. Other factors for the inability to enforce regulatory law, such as insufficient skilled and committed human resources, the presence of corruption, as well as financial resource scarcity, were revealed in the review. From the situational analysis, the possibility of building a robust quality assurance system in the near future through a quality by design approach under existing resource limitations was discussed. The pharmaceutical sector in Africa faces significant challenges, including the prevalence of poor-quality medicines and weak regulatory enforcement. Tackling these challenges are vital for enhancing health outcomes throughout the continent through the provision of high-quality medicines. Trending towards quality by design in the quality assurance system under prevailing financial scarcity can be very beneficial.